2013
DOI: 10.1089/jamp.2012.0977
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Safety and Efficacy of Fluticasone/Formoterol Combination Therapy in Asthma

Abstract: Fluticasone/formoterol had a good safety and efficacy profile over the 6- and 12-month study periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 53 publications
(62 reference statements)
5
28
0
Order By: Relevance
“…Flutiform ® (FP/FORM) is an inhaler product containing a combination of fluticasone propionate (FP) and formoterol fumarate (FORM), approved for maintenance use in asthma following a comprehensive series of studies [1][2][3][4][5][6][7][8][9][10]. It is currently available within a conventional hydrofluoroalkane-propelled pressurised metered-dose inhaler (pMDI).…”
Section: Introductionmentioning
confidence: 99%
“…Flutiform ® (FP/FORM) is an inhaler product containing a combination of fluticasone propionate (FP) and formoterol fumarate (FORM), approved for maintenance use in asthma following a comprehensive series of studies [1][2][3][4][5][6][7][8][9][10]. It is currently available within a conventional hydrofluoroalkane-propelled pressurised metered-dose inhaler (pMDI).…”
Section: Introductionmentioning
confidence: 99%
“…An extensive clinical dataset exists for FP/FORM administered via a pMDI (Table 2) [29][30][31][32][33][34][35][36][37][38]. Furthermore, long-term data from two clinical studies have demonstrated good efficacy, safety, and tolerability with this ICS/LABA combination, including a low rate of exacerbations, over study periods of up to 60 weeks [33,35]. Real-world data from non-interventional studies in over 4000 patients with asthma support the effectiveness and safety/ tolerability of FP/FORM pMDIs in general clinical practice [29,37].…”
Section: Fp/form Clinical Datamentioning
confidence: 99%
“…The therapeutic efficacy of the fluticasone propionate/formoterol combination has been evaluated in nine multicenter phase III clinical studies [32][33][34][50][51][52][53][54][55] on patients aged ≥ 12 years [32][33][34][50][51][52][53][54][55] or aged ≥ 18 years [32,33] with mild to moderate [53,54], moderate to severe [32,33,50,51,55] or mild to moderate-severe persistent asthma [34,52] [ Table 2]. Further studies and pooled analyses are to be expected …”
Section: Therapeutic Efficacy and Tolerabilitymentioning
confidence: 99%
“…However, the fluticasone/formoterol combination has a more rapid bronchodilator effect than the fluticasone propionate/salmeterol combined treatment, defined as the first postdose measurement with FEV 1 ≥ 12% of the corresponding pre-dose value (p = 0.001) [32,37]. Moreover, the fluticasone/formoterol combination is well tolerated at all considered doses [32][33][34][50][51][52][53][54][55], including in long-term treatments up to 12 months [52].…”
Section: Alternative Reliever Treatments Include Inhaled Anticholinermentioning
confidence: 99%